Total Flavonoid Content, Antibacterial Activity and In Silico Toxicity Prediction of Ethanolic Extract from Murraya koenigii Leaves against Streptococcus mutans - Haris Munandar Nasution; Nasri Nasri; Ziza Putri Aisyia Fauzi; Zulmai Rani; Ainil Fithri Pulungan; Vera Estefania Kaban (Journal of Pharmascience, 2026)
Dental caries is a chronic disease exclusive to humans and remains one of the most prevalent oral health problems worldwide. The increasing emergence of antibiotic resistance and the adverse effects associated with conventional antimicrobials have encouraged the exploration of natural plant-derived compounds for caries prevention. Murraya koenigii leaves are widely used as a culinary ingredient and are known to possess various therapeutic properties, including antioxidant, antibacterial, anti-inflammatory, and hepatoprotective activities. This study aimed to evaluate the total flavonoid content, antibacterial activity, and in silico toxicity profile of the ethanolic extract of M. koenigii leaves against Streptococcus mutans, a primary cariogenic pathogen. Total flavonoid content was determined using the aluminum chloride colorimetric method, while antibacterial activity was assessed using the agar disk diffusion assay. The toxicity profile of major flavonoid constituents was further analyzed using in silico ADMET prediction tools. The results showed that the ethanolic extract of M. koenigii leaves contained a high total flavonoid content (281.83 ± 10.23 mg QE/g extract) and exhibited strong antibacterial activity against Streptococcus mutans, producing inhibition zones ranging from 14.4 to 19.4 mm in a concentration-dependent manner. In silico analysis indicated that the major flavonoid constituents possessed favorable pharmacokinetic characteristics with low predicted toxicity risks. These findings suggest that the ethanolic extract of M. koenigii leaves is rich in flavonoids and demonstrates significant antibacterial potential, supporting its promise as a natural antibacterial agent for oral health applications. Further studies focusing on compound isolation, formulation development, and in vivo validation are recommended.